Magnetism, electron transport and effect of disorder in CoFeCrAl. (19th May 2015) - Kharel, P; Zhang, W; Skomski, R; Valloppilly, S; Huh, Y; Fuglsby, R; Gilbert, S; Sellmyer, D J
Abstract: Structural, electronic, and magnetic properties of a Heusler-type CoFeCrAl alloy have been investigated experimentally and by model calculations, with a focus on the alloy's spin-gapless semiconductivity. The as-quenched samples are ferrimagnetic at room temperature with a Curie temperature of about 456 K, which increases to 540 K after vacuum annealing at 600 °C for 2 h. The saturation magnetizations of the as-quenched and 600 °C-annealed samples are 1.9  µ B /f.u. and 2.1 µ B /f.u., respectively, which are very close to the value predicted by the Slater–Pauling curve. The resistivity shows a nearly linear decrease with increasing temperature, from about 930  µ Ω cm at 5 K to about 820  µ Ω cm at 250 K, with d ρ/ d T of about  −5   ×   10 −7  Ω cm K −1 . We explain this high resistivity and its temperature dependence as imperfect spin-gapless semiconducting behavior, with a negative band-gap parameter of 0.2 eV.